Application of membrane-selective electrodes for the determination of Tiemonium methylsulphate - Lobna A. Hussein (Faculty of Pharmacy, Cairo University, 2017)
Three ion selective electrodes were developed for the quantification of Tiemonium methylsulphate (TIM). Two of these sensors involve the construction of water insoluble ion-association complexes; namely sensor1 TIM-phosphotungstate (TIM-PT) and sensor 2 TIM-Reinecke (TIM-R). Molecular recognition elements have extensive applications in electrochemical sensors with a significant potential for future development thus a third electrode utilizing molecularly imprinted polymer was constructed; sensor 3 TIM-MIP. The proposed sensors showed fast, stable Nernstian responses of 56.4, 56.1and 57.5 mV/decade for sensors 1, 2 and 3, respectively, across a relatively wide TIM concentration range (1 × 10−4 to 1 × 10−2 mol L−1 for sensors 1 and 2 and 1 × 10-5 to 1 × 10-2 mol L−1 for sensor 3) in the pH range of 2-7. Sensor 1 and sensor 2 can be used for five weeks while sensor 3 for 65 days without a significant change in sensitivity. The suggested method was used to determine TIM in dosage forms. No measurable difference was obtained when the result statistically compared with respect to accuracy and precision with reported HPLC method.